Intra‐epidermal nerve endings progress within keratinocyte cytoplasmic tunnels in normal human skin. Issue 4 (14th February 2020) - Talagas, Matthieu; Lebonvallet, Nicolas; Leschiera, Raphael; Elies, Philippe; Marcorelles, Pascale; Misery, Laurent
Abstract: Intra‐epidermal nerve endings, responsible for cutaneous perception of temperature, pain and itch, are conventionally described as passing freely between keratinocytes, from the basal to the granular layers of the epidermis. However, the recent discovery of keratinocyte contribution to cutaneous nociception implies that their anatomical relationships are much more intimate than what has been described so far. By studying human skin biopsies in confocal laser scanning microscopy, we show that intra‐epidermal nerve endings are not only closely apposed to keratinocytes, but can also be enwrapped by keratinocyte cytoplasms over their entire circumference and thus progress within keratinocyte tunnels. As keratinocytes must activate intra‐epidermal nerve endings to transduce nociceptive information, these findings may help understanding the interactions between the keratinocytes and nervous system. The discovery of these nerve portions progressing in keratinocyte tunnels is a strong argument to consider that contacts between epidermal keratinocytes and intra‐epidermal nerve endings are not incidental and argue for the existence of specific and rapid paracrine communication from keratinocytes to sensory neurons.